Confiscation of Copyrights in Investigations of Criminal Actions in the Field of Taxation and Tax Collection - Chakim Yudha Perdana; Sulistyanta (MultiTech Publisher, 2024)
This article discusses the confiscation of copyright as a form of intellectual property in the investigation of criminal acts in the field of taxation and tax collection. Copyright legal provisions recognize the moral right of creators to defend their rights from things that are detrimental to their personal honor or reputation through certain legal measures, while tax law regulates the authority to carry out confiscation in the event of criminal acts in the field of taxation or unpaid tax debts. This can cause conflicts between legal provisions in their implementation and raise questions about how to confiscate copyright as an intangible movable object. To answer this question, the author carried out a juridical analysis of the provisions of Copyright law and confiscation, prepared arguments for the relevance of Copyright confiscation, and drew conclusions inductively based on the results of the analysis. With the conclusion that there is a legal basis for confiscation related to investigations, but regarding tax collection it does not have sufficient legal basis and requires further regulation of confiscation authority. The exercise of confiscation authority that is not against the law will not conflict with the Creator's legal efforts to defend his rights.